Theoretical analіz problems of accentuation for character (Actual Problems of Psychology in Educational Institutions, 2019)
The article highlights the importance of character in humanlife. ​ It is shown that character accentuations are extreme expressions of thenorm. ​ The negative influence of accentuations on the formation of personality isnoted. ​ A theoretical analysis of literature on the subject of research was made. Itis shown that the nature of the accentuation of the character is the sameindividual features, which tends to a potential transition to a certain pathologicalstate.
Keywords: character; character accentuation; pathology; theoretical analysis